2021
DOI: 10.3390/ijerph18126200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper Sulphate and Cadmium Chloride on Non-Human Primate Sperm Function In Vitro

Abstract: In order to address the large percentage of unexplained male infertility in humans, more detailed investigations using sperm functional tests are needed to identify possible causes for compromised fertility. Since many environmental and lifestyle factors might be contributing to infertility, future studies aiming to elucidate the effect of such factors on male fertility will need the use of appropriate research models. The current study aimed to assess the effects of two heavy metals, namely copper sulphate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Even despite lower concentrations of Cu in SP, all authors mention the adverse effect on spermatozoa cells including decreased motility and viability and higher incidence of disrupted acrosomes. The disturbing effect of Cu was also proven in in vitro conditions [ 43 , 44 , 45 ]. Concerning redox homeostasis of sperm cells, we analyzed nonenzymatic parameters as well as enzymatic parameters including GPx and SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Even despite lower concentrations of Cu in SP, all authors mention the adverse effect on spermatozoa cells including decreased motility and viability and higher incidence of disrupted acrosomes. The disturbing effect of Cu was also proven in in vitro conditions [ 43 , 44 , 45 ]. Concerning redox homeostasis of sperm cells, we analyzed nonenzymatic parameters as well as enzymatic parameters including GPx and SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed a decrease in testes and epididymis weight and a significant increase in sperm abnormalities. Long-term, high-dose Cu 2+ exposure was found to be negatively correlated with sperm motility, viability and vitality, acrosome intactness, and hyperactivation in a study performed on the vervet monkey ( Chlorocebus aethiops ), the chacma baboon ( Papio ursinus ), and the rhesus monkey ( Macaca mulatta ) used as models for reproductive studies [ 137 ].…”
Section: Male Reproductive Toxicity Of Micronutrient Metalsmentioning
confidence: 99%
“…Cadmium and copper are two heavy metals that may adversely affect the reproductive health of humans, especially male fecundity, after exposure [16]. It was shown that Cu 2+ immobilization in metakaolin-based geopolymer consists of chemical incorporation into the geopolymer matrix and was pH dependent as a large amount of Cu 2+ was precipitated in the form of gerhardtite (low pH) or tenorite and spertiniite (high pH) [17].…”
Section: Introductionmentioning
confidence: 99%